PENGARUH VARIASI RESIN EPOKSI TERHADAP KUAT TEKAN PADA MORTAR POLIMER BERBAHAN DEBU BATU - Idris Setianto, Achmad; Elvira, Elvira; Sulandari, Eti; Herwani, Herwani; Nurhayati, Nurhayati; Rabihati, Etty (Penerbit Lafadz Jaya, 2026)
Polymer mortar is an alternative material developed by utilising epoxy resin as a binder and stone dust as a fine aggregate. This study aims to analyse the effect of epoxy resin variation on the compressive strength of stone dust-based polymer mortar. The epoxy resin variations used in this study were 10%, 15%, and 20% of the material weight. Compressive strength testing was conducted at ages of 1, 2, 7, 14, and 21 days. The results showed that an increase in the percentage of epoxy resin significantly improved the mechanical properties of polymer mortar. At a variation of 10%, a compressive strength of 9.03 MPa was obtained at 21 days. Meanwhile, a variation of 20% resulted in a compressive strength of 17.71 MPa. This study indicates that an increase in the epoxy mixture content and a longer testing age affect the increase in the compressive strength of stone dust-based polymer mortar. These results also support the application of sustainable construction principles through the use of alternative materials.